Representation of Homophobia in Dallas Buyers Club - Ichsan Agung Mulyana; Triyono Lukmantoro, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Film, functions as entertainment, is able to provide enjoyment to the audience, but sometimes as informative function could deliver any ideological messages. For example, hateful and discriminative message toward minority such as LGBT. Dallas Buyers Club presents AIDS as a major theme, along with hatred toward LGBT know as homophobia. Homophobia can also be a fear of self when identified as homosexual. The film offers insight into the homophobia that has always associated with AIDS, though not necessarily the case. Homophobia can also happen to people with non-LGBT AIDS stigma known by LGBT groups as carriers of the AIDS virus This study aims to study how representation of homophobia in Dallas Buyers Club, using qualitative method along with The Codes of Television analysis. The theories are Representation Theory, Film and Ideologi and Homophobia. The findings of this reviews embody 3 points, such as : 1) Hatred to LGBT and non-LGBT AIDS sufferer is mostly expressed by mockery and insult, either verbally or non-verbally 2) Ron character is depicted as a hypocrite when he needs particular things from gay character 3) The basic of homophobic behaviour shows that masculine ideology dominates to repress gay character which alternated as feminine role